Extended Writing Project: An Experimental Study On How to Encourage Students to Work Collaboratively - Fauziah, Humairah (JOURNAL OF EDUCATION FOR ALL, 2024)
This paper reports students’ involvement in a classroom project, called extended writing project (EWP), to help undergraduate students write their first essay. The EWP aimed at encouraging the students to work collaboratively with their peers and teacher, give and respond to feedbacks, and work independently outside the classroom. During the process of EWP, we equipped the students with a mini book to help them record the whole activities and monitor their progress. We involved 20 first year undergraduate students enrolled in a writing course, which was a compulsory course to prepare the students for writing their research project and thesis in the final year of their degree program. We used several instruments such as pre-posttest to know the students’ writing improvement, open-ended questionnaire to obtain their perceptions toward the EWP, the mini book to obtain a comprehensive understanding on the students’ activities including kinds of feedbacks provided by their peers, and an informal interview to know how they dealt with the feedbacks. The results indicated that EWP positively affected the students’ writing skill. Furthermore, in term of writing components (fluency, grammar, vocabulary, spelling, and content), EWP was able to improve all those aspects but spelling. The open-ended questions informed that the students felt that EWP was able to increase their confidence and motivation to write. The redundancy of writing draft, however, exhausted them all the time.